HLA-DR-Positive NK Cells Expand in Response to Mycobacterium Tuberculosis Antigens and Mediate Mycobacteria-Induced T Cell Activation - Kust, Sofya A.; Streltsova, Maria A.; Panteleev, Alexander V.; Karpina, Natalya L.; Lyadova, Irina V.; Sapozhnikov, Alexander M.; Kovalenko, Elena I. (Frontiers in Immunology, 2021)
NK cells play an important role in the control of tuberculosis infection: they are not only able to kill the infected cells, but also control the activity of macrophages and development of the adaptive immune response. Still, there is little information on the role of specific NK cell subsets in this network. In this study, we focused on the mycobacteria-driven responses of the NK cells expressing HLA-DR – a type of MHC class II. We have revealed that this subset is increased in the peripheral blood of patients with primary diagnosed tuberculosis, and expands in response to in vitro stimulation with ultrasonically destroyed Mycobacterium tuberculosis cells (sonicate). The expanded HLA-DR+ NK cells had less differentiated phenotype, higher proliferative activity and increased expression of NKp30 and NKp46 receptors. HLA DR+CD56dim NK cells showed higher IFNγ production and degranulation level than the respective HLA-DR‒ NK cells in response to both 24 h and 7 day stimulation with sonicate, while HLA DR+CD56bright NK cells mostly demonstarted similar high responsiveness to the same stimulating conditions as their HLA DR‒CD56bright counterparts. After preliminary incubation with destroyed mycobacteria, cytokine-activated HLA-DR-expressing NK cells were able to mediate mycobacteria-induced and HLA-DR-dependent cytokine production in autologous CD4+ T cells. Thus, functionally active HLA-DR+ cells seem to be one of the NK cell subsets providing an important link to the adaptive immunity.